Guided Imagery Technique Implementation Reducing Primigravida Pregnancy Anxiety Before Childbirth Delivery - Andriani, Yessi; Amalia, Endra; Primal, Def (JOSING: Journal of Nursing and Health, 2021)
Anxiety is the most common psychiatric condition found throughout the world. Anxiety in pregnancy is an emotional reaction that occurs in pregnant women related to the concern of the mother with the welfare of herself and her fetus. Guided imagery is the development of mental functions that express oneself dynamically through a psychophysiological process involving all senses and bringing about changes in behavior, perception, or physiological responses with someone's guidance or through the media. This scientific case study aims to determine the application of nursing care to primigravida mothers in dealing with the labor process using guided imagery techniques. The data collection techniques used were interviews, observation, physical examination, and documentation study. This scientific paper shows that there is a decrease in the level of anxiety in the patient after doing the guided imagery technique for 3 meetings. Based on these results, it can be concluded that the intervention from journals related to nursing care in primigravida mothers who experience anxiety has been implemented well. The results of this scientific case study are expected to be implemented as a basis for developing nursing care management and assisting nurses to increase client’s satisfaction with caring provided. Keywords: anxiety, guided imagery, primigravida pregnancy.